2011
DOI: 10.1007/s10555-011-9277-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair: the culprit for tumor-initiating cell survival?

Abstract: The existence of “tumor-initiating cells” (TICs) has been a topic of heated debate for the last few years within the field of cancer biology. Their continuous characterization in a variety of solid tumors has led to an abundance of evidence supporting their existence. TICs are believed to be responsible for resistance against conventional treatment regimes of chemotherapy and radiation, ultimately leading to metastasis and patient demise. This review summarizes DNA repair mechanism(s) and their role in the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…Oncomine analyses showed that numerous human cancers, such as of the prostate, brain, cervix, head and neck, kidney, bladder and pancreas, displayed elevated levels of DNA repair proteins [for review see ref. (154)]. Moreover, in melanoma, there is considerable evidence that DNA repair genes are upregulated in metastases compared with primary tumors (57, 155).…”
Section: Role Of Cell Cycle Checkpoint Control and Dna Repair Genes Imentioning
confidence: 99%
“…Oncomine analyses showed that numerous human cancers, such as of the prostate, brain, cervix, head and neck, kidney, bladder and pancreas, displayed elevated levels of DNA repair proteins [for review see ref. (154)]. Moreover, in melanoma, there is considerable evidence that DNA repair genes are upregulated in metastases compared with primary tumors (57, 155).…”
Section: Role Of Cell Cycle Checkpoint Control and Dna Repair Genes Imentioning
confidence: 99%
“…Increased expression of major DNA repair proteins, including BRCA1, ATR and ATM, has been observed in pancreatic, breast and prostate CSCs [156][157][158]. Reduced DNA repair capacity in CSCs has also been reported (reviewed by Wang [159]).…”
Section: Dna Repairmentioning
confidence: 99%
“…When the DNA repair cascades are unable to adequately fix the damage, cell-cycle checkpoint components are activated which can recruit additional DNA repair components or activate apoptosis. Data from many studies imply that CSCs have elevated levels of DNA repair [53][54][55][56][57][58][59][60][61], these provide one explanation for the resistance of some tumor types to platinum agents.…”
Section: Chemoresistance Of Cancers Stem Cells By Enhanced Dna Repairmentioning
confidence: 99%